(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Studies carried out to develop a technique for the preservation of cow’s milk in raw condition using hydrogen peroxide (H2O2) as a preservative. Fresh cows milk was collected and experiments were conducted by four treatments in order to achieve the optimum condition of storage. The treatments were with various concentration of H2O2 starting from 0.05 %, 0.1 %, 0.2 %, 0.3 %, 0.4 %, & 0.5 %. Treated milk with 0.05 % concentration of H2O2 had storage period of 20 days compared to that of the control one (5 days only) in refrigerated temperature (±8°C). On the other hand hydrogen peroxide treated milk (0.05 %) had a storage period of 8 hours at room temperature (±28°C). Results also showed that the higher concentration of H2O2 had no effect on storage period than that of control. Milk products like kheer and halawa prepared by treated milk and stored for 20 days showed almost nil growth of total coliform and E. coli which means that food products prepared from hydrogen peroxide treated milk is safe for human consumption. Key words: Raw, Storage, Hydrogen peroxide, Preservative, keeping quality, Pasteurization, deteriorated, MPN. Bangladesh J. Sci. Ind. Res. 42(3), 317-326, 2007